2019
DOI: 10.1007/s11427-018-9554-5
|View full text |Cite
|
Sign up to set email alerts
|

Metal-dependent anaerobic methane oxidation in marine sediment: Insights from marine settings and other systems

Abstract: Anaerobic oxidation of methane (AOM) plays a crucial role in controlling global methane emission. This is a microbial process that relies on the reduction of external electron acceptors such as sulfate, nitrate/nitrite, and transient metal ions. In marine settings, the dominant electron acceptor for AOM is sulfate, while other known electron acceptors are transient metal ions such as iron and manganese oxides. Despite the AOM process coupled with sulfate reduction being relatively well characterized, researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 79 publications
0
26
0
Order By: Relevance
“…To the best of our knowledge, there is no representative pure culture of Fe-AOM microorganisms from the marine sediment ( Liang et al, 2019 ). But some microorganisms were suspected of being related to metal-AOM in various earlier studies, which suggested that ANME-1, ANME-3 ( Beal et al, 2009 ), ANME-2a, 2c ( Scheller et al, 2016 ), ANME-2d ( Methanoperedens nitroreducens ) ( Ettwig et al, 2016 ; Shen et al, 2019 ), Candidatus Methanoperedens ferrireducens ( Cai et al, 2018 ), or Methanosarcina acetivorans ( Yan et al, 2018 ) might be involved in Fe-AOM.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is no representative pure culture of Fe-AOM microorganisms from the marine sediment ( Liang et al, 2019 ). But some microorganisms were suspected of being related to metal-AOM in various earlier studies, which suggested that ANME-1, ANME-3 ( Beal et al, 2009 ), ANME-2a, 2c ( Scheller et al, 2016 ), ANME-2d ( Methanoperedens nitroreducens ) ( Ettwig et al, 2016 ; Shen et al, 2019 ), Candidatus Methanoperedens ferrireducens ( Cai et al, 2018 ), or Methanosarcina acetivorans ( Yan et al, 2018 ) might be involved in Fe-AOM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been discovered that other Ca. Methanoperedens strains coupled AOM to the reduction of iron oxides and other metal oxides (Cai et al, 2018;Liang et al 2019;Leu et al, 2020). (Evans et al, 2015;Vanwonterghem et al, 2016).…”
Section: Diversity and Distribution Of Anaerobic Alkaneoxidizing Archaeamentioning
confidence: 99%
“…However, it should be cautioned that the biochemistry of ANME is largely unknown and differences with methanogenic pathways are anticipated ( Timmers et al, 2017 ). Nonetheless, the biochemical-based AOM pathway provides a working model for mechanistic understanding of the growing literature describing respiratory AOM by individual ANME using a variety of electron acceptors including Fe(III) ( Raghoebarsing et al, 2006 ; Beal et al, 2009 ; Haroon et al, 2013 ; Ettwig et al, 2016 ; Cai et al, 2018 ; He et al, 2018 ; Liang et al, 2019 ; Luo et al, 2019 ; Aromokeye et al, 2020 ; Leu et al, 2020 ).…”
Section: Reverse Methanogenesismentioning
confidence: 99%